2019
DOI: 10.1530/joe-18-0402
|View full text |Cite
|
Sign up to set email alerts
|

Role of GPER in the anterior pituitary gland focusing on lactotroph function

Abstract: Ovarian steroids control a variety of physiological functions. They exert actions through classical nuclear steroid receptors, but rapid non-genomic actions through specific membrane steroid receptors have been also described. In this study, we demonstrate that the G-protein-coupled estrogen receptor (GPER) is expressed in the rat pituitary gland and, at a high level, in the lactotroph population. Our results revealed that ~40% of the anterior pituitary cells are GPER positive and ~35% of the lactotrophs are G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Increased GPER activity with age may be attributed to the decreased amount of E2 with advanced age. Camilletti et al 30 have found that local GPER expression is regulated negatively by E2, progesterone, and lack of ovarian steroids after an ovariectomy significantly increases pituitary GPER expression. They have also shown a rapid E2 stimulatory effect on PRL secretion mediated by GPER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased GPER activity with age may be attributed to the decreased amount of E2 with advanced age. Camilletti et al 30 have found that local GPER expression is regulated negatively by E2, progesterone, and lack of ovarian steroids after an ovariectomy significantly increases pituitary GPER expression. They have also shown a rapid E2 stimulatory effect on PRL secretion mediated by GPER.…”
Section: Discussionmentioning
confidence: 99%
“…They have also shown a rapid E2 stimulatory effect on PRL secretion mediated by GPER. 30,31 The GPER mediates the rapid effects of estrogen and aldosterone. Current studies indicate that GPER activation regulates blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the estradiol-mediated effect on proliferation of lactotropic cells in primary culture seems not to be due to GPER signaling [83]. The physiological roles of GPER in the pituitary are still not completely understood, but it seems to be involved in modulation of secretion of gonadotropins [84] and PRL [70] (Figure 3). At the same time, expression of the GPER gene is under estrogen-mediated genomic signaling [70] (Figure 3).…”
Section: Effects Of Estradiol On Differentiated Lactotropic Cells In mentioning
confidence: 99%
“…Physiological and pathophysiological mechanisms of estrogen (E) action on proliferation, growth and secretion of lactotropic (PRL) cells are probably largely mediated by nuclear estrogen receptor (ER) α. Membrane G-protein-coupled estrogen receptor 1 (GPER)-mediated estrogen signaling seems to be more involved in antiproliferative and apoptotic actions in the pituitary and may contribute to rapid secretion of PRL under physiological conditions. Its expression is under ERα-mediated nuclear signaling[15,59,[68][69][70].…”
mentioning
confidence: 99%
“…The genomic effects of estrogen are relatively slow and take place in hours while some 'pregenomic' or rapid actions involving second messenger activation have also been described [13,23,24]. A membrane-bound G-protein coupled ER (GPER1) belonging to G-protein coupled receptor (GPCR) superfamily has recently been defined [13,25,26]. This receptor was shown to be rapidly activated upon estrogen binding and induce stimulation of adenylyl cyclase pathway [13,24].…”
Section: Introductionmentioning
confidence: 99%